Method for testing static color development of thermo-sensitive paper
By adjusting the proportions of thermal dye dispersion, color developer dispersion, and sensitizer dispersion, preparing mixed coating liquid, and conducting static coloring tests within a specific temperature range, the problem of inappropriate proportions in the existing test methods is solved, and the smooth completion of the test and the stable increase of the color density value are achieved.
Patent Information
- Application Number
- CN202411927700.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-11
AI Technical Summary
The existing thermally sensitive static color testing method cannot complete the static color testing because the proportions of thermally sensitive dye dispersion, color developer dispersion and sensitizer dispersion are inappropriate.
By adjusting the ratio of the thermal dye dispersion, the color developer dispersion, and the sensitizer dispersion, a mixed coating liquid is prepared, and a static coloration test is performed within a specific temperature range to record the color density value.
The color density value is achieved within the test temperature range of 60-130℃, and the saturated color density value is achieved, ensuring the smooth completion of the static color growth test.
Smart Images

Figure CN119804835A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fine chemicals, and in particular to a static color development test method for thermal paper. Background Art
[0002] Thermal dyes have always been a hot area of dye research due to their wide application and rapid response characteristics. The main types include phthalocyanines, fluoranes, fluorenes, phenothiazines, phenoxazines and coumarins. Among them, fluorane dyes have attracted much attention due to their diverse structures, high sensitivity, stable properties and wide chromatographic range, and have been widely used in the field of thermal materials. However, the existing thermal materials based on fluorane dyes have poor light resistance. The main reason is that the high-energy ultraviolet light in sunlight can destroy the fluorane in the thermal material, causing the pattern to fade or even disappear after thermal printing.
[0003] In the existing thermal-sensitive static color test method, the static color test cannot be completed due to the inappropriate ratio of the thermal-sensitive dye dispersion, the developer dispersion and the sensitizer dispersion. Summary of the invention
[0004] In view of the above analysis, the present invention aims to provide a static color development test method for thermal paper, so as to solve the problem that the static color development test cannot be completed due to the inappropriate ratio of the thermal dye dispersion, the developer dispersion and the sensitizer dispersion used in the existing thermal static color development test method.
[0005] The purpose of the present invention is mainly achieved through the following technical solutions:
[0006] The present invention provides a method for testing the static color development of thermal paper, comprising the following steps:
[0007] Step a: preparing a thermosensitive dye dispersion, a developer dispersion and a sensitizer dispersion respectively;
[0008] Step b: Take 8-12 parts of thermosensitive dye dispersion, 12-18 parts of developer dispersion, 6-9 parts of sensitizer dispersion, 5-10 parts of kaolin and 8-12 parts of deionized water, mix and stir to obtain a mixed coating solution;
[0009] Step c: coating the mixed coating liquid on paper, performing a static color development test, and recording the color density value;
[0010] In step a, the raw materials for preparing the thermosensitive dye dispersion include a fluorine-containing fluorane compound having a structure of formula I:
[0011]
[0012] Optionally, in step a, preparing the thermosensitive dye dispersion includes: weighing each raw material according to weight, mixing and grinding, to obtain the thermosensitive dye dispersion.
[0013] Optionally, the raw materials for preparing the thermosensitive dye dispersion liquid include, by weight: 8-12 parts of fluorine-containing fluorane compounds, 1-5 parts of polyvinyl alcohol, and 15-25 parts of deionized water.
[0014] Optionally, in step b, the stirring time is 0.5-2 hours.
[0015] Optionally, in step c, the temperature for performing the static color test is 60-130°C.
[0016] Optionally, in step c, the interval for recording the color density value is once every 10°C.
[0017] Optionally, in step a, preparing the developer dispersion includes: taking 8-12 parts of bisphenol A, 1-2 parts of polyvinyl alcohol, and 18-22 parts of deionized water, and grinding to obtain the developer dispersion.
[0018] Optionally, in step a, preparing the sensitizer dispersion includes: taking 8-12 parts of benzyl-2-naphthyl ether, 1.5-2.5 parts of polyvinyl alcohol, and 18-22 parts of deionized water, and grinding to obtain the sensitizer dispersion.
[0019] Optionally, the fluorine-containing fluorane compound having the structure of formula I is prepared by the following method:
[0020] Step 1: Add 2-(2-hydroxy-4-diethylaminobenzoyl)benzoic acid, 3,5-bis(trifluoromethylphenol) and a strong acid into a reaction container to cause a condensation reaction;
[0021] Step 2: Cooling down, adding an organic solvent to the reaction system, and then slowly adding an alkaline solution, heating up, refluxing and stirring, causing a ring-closing reaction to occur, and obtaining a reaction solution;
[0022] Step 3: Separate the reaction solution to obtain an organic phase, wash the organic phase with water until it is neutral, separate the phases, collect the neutral organic phase, remove the organic solvent by distillation under reduced pressure, and dry to obtain a solid fluorine-containing fluorane compound.
[0023] Optionally, in step 1, the strong acid is a mixed strong acid.
[0024] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0025] The present invention controls the ratio of a thermosensitive dye dispersion, a developer dispersion and a sensitizer dispersion so that in a static color development test, the dye will neither develop color prematurely nor have a sharp increase in color density value, and can ensure that the color density value increases steadily within a test temperature range of 60 to 130° C., and then reaches a saturated color density value, thereby ensuring smooth completion of the static color development test.
[0026] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can be obvious from the description or understood by practicing the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0028] Figure 1 The UV-visible absorption spectra of the fluorine-containing light-resistant fluorane thermosensitive dye prepared in Example 1 and the existing thermosensitive dye D-5 in the color-developed state;
[0029] Figure 2 This is a test chart of the static color development performance of the fluorine-containing light-resistant fluorane thermosensitive dye prepared in Example 1 and the existing thermosensitive dye D-5;
[0030] Figure 3 It is a test chart of the static color performance of Preparation Example 1 and Comparative Examples 9-11. DETAILED DESCRIPTION
[0031] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0032] The present invention provides a method for testing the static color development of thermal paper, comprising the following steps:
[0033] Step a: preparing a thermosensitive dye dispersion, a developer dispersion and a sensitizer dispersion respectively;
[0034] Step b: Take 8-12 parts of thermosensitive dye dispersion, 12-18 parts of developer dispersion, 6-9 parts of sensitizer dispersion, 5-10 parts of kaolin and 8-12 parts of deionized water, mix and stir to obtain a mixed coating solution;
[0035] Step c: Apply the mixed coating liquid on paper, perform a static color development test, and record the color density value.
[0036] In step a, the raw materials for preparing the thermosensitive dye dispersion include a fluorine-containing fluorane compound having a structure of formula I:
[0037]
[0038] The fluoran compounds of the present invention contain fluorine elements, and the fluorine elements have a higher bond energy, which makes the chemical structure of the fluoran compounds containing fluorine more stable and difficult to be decomposed or destroyed by ultraviolet rays. In addition, the electronegativity of fluorine atoms is strong, which can effectively reduce the oxidation or degradation of other groups in the material, thereby further enhancing the weather resistance and ultraviolet resistance of the material. Therefore, the fluorine-containing light-resistant fluoran thermosensitive dye provided by the present invention can be used for long-term exposure to outdoor or ultraviolet environments. Compared with the existing D-5 thermosensitive dye, under the same color development conditions, the thermal paper after color development has a lower pattern fading rate after aging test, proving that the thermosensitive material of the thermosensitive dye has good light resistance. Specifically, the thermal paper after color development using the fluorine-containing light-resistant fluoran compounds of the present invention as the thermosensitive dye has a color density change rate before and after sunlight of 18%-22% when it is not color developed, which is much lower than the 200% of the prior art (see Table 1); when saturated color development is 8.3%-11.5%, which is much lower than the 26.3% of the prior art (see Table 1).
[0039] The fluorine element in the fluorane compound of the present invention exists in the form of trifluoromethyl groups, and there are two trifluoromethyl groups, which effectively increases the content of the fluorine element and further enhances the weather resistance and ultraviolet resistance of the material.
[0040] It should be noted that in the present invention, the two trifluoromethyl groups are located at the meta position on the benzene ring and at the 1,3 position. This is because:
[0041] 1. Because the fluorine element has a higher bond energy, the chemical structure of the fluorine-containing fluoran compounds is more stable and difficult to be decomposed or destroyed by ultraviolet rays. In addition, the electronegativity of the fluorine atom is strong, which can effectively reduce the oxidation or degradation of other groups in the material, thereby further enhancing the weather resistance and UV resistance of the material. In theory, the higher the content of fluorine, the better. If fluorine atoms are directly introduced into the benzene ring, it is limited by the number of substitution sites of the benzene ring and is not easy to increase the fluorine content. Introducing the fluorine element in the form of trifluoromethyl can achieve the one-time introduction of 3 fluorine atoms at the substitution site of a single benzene ring, which is a relatively efficient introduction strategy. However, compared to directly introducing fluorine atoms into the benzene ring, the steric hindrance of the trifluoromethyl group is larger, and after a large amount of strongly electronegative fluorine atoms are introduced, it is not conducive to the condensation of phenol and ketoacid, resulting in a low raw material conversion rate or even completely unable to form a fluoran dye. The present invention reduces the influence of the steric effect by selecting suitable raw materials to adjust the distribution position of the trifluoromethyl group in the benzene ring.
[0042] 2. If the two trifluoromethyl groups are located at the 2,3, 2,4, 2,5, 2,6 or 3,4 positions, there are certain technical difficulties in the dye synthesis or post-processing process. Among them, the di-trifluoromethylphenols at the 2,3, 2,4 and 2,5 positions are asymmetric structures, in which one of the trifluoromethyl groups is located adjacent to the phenolic hydroxyl group. The steric hindrance and strong electronegativity of the trifluoromethyl group lead to a decrease in the activity of the phenolic hydroxyl group, and it is difficult to close the ring to form a fluorane mother nucleus after condensation; the phenolic hydroxyl group in the di-trifluoromethylphenol at the 2,6 position is adjacent to two trifluoromethyl groups at the same time, and the condensation reaction cannot occur at all; the di-trifluoromethylphenol at the 3,4 position has certain reactivity, but due to the asymmetry of its structure, the two dye molecules formed after condensation and ring closure are isomers of each other, which makes post-processing separation difficult.
[0043] 3. The dye color development process is that the lactone ring opens to form carboxyl anions, and at the same time the positive charge is transferred to the nitrogen atom of the N,N-diethylamino group. The benzene ring connected to it is further transformed to form a conjugated planar structure. The introduction of two strongly electronegative trifluoromethyl groups into the dye molecular structure is conducive to stabilizing the negative charge of the carboxyl anion, making the charge distribution of the dye molecule in the colored state more uniform and stable. Compared with the commercial dye D-5 substituted with two methyl groups, it has better stability after color development and is not easy to fade.
[0044] The fluorine-containing fluorane compound of formula I is prepared by the following method, comprising the following steps:
[0045] Step 1: Add 2-(2-hydroxy-4-diethylaminobenzoyl)benzoic acid, 3,5-bis(trifluoromethyl)phenol and a mixed strong acid into a reaction container to cause a condensation reaction;
[0046] Step 2: Cooling down, adding an organic solvent to the reaction system, and then slowly adding an alkaline solution, heating up, refluxing and stirring, causing a ring-closing reaction to occur, and obtaining a reaction solution;
[0047] Step 3: Separate the reaction solution to obtain an organic phase, wash the organic phase with water until it is neutral, separate the phases, collect the neutral organic phase, remove the organic solvent by distillation under reduced pressure, and dry to obtain a solid fluorine-containing fluorane compound.
[0048] Specifically, in step 1, the reaction temperature of the condensation reaction is 25-100° C., for example, 25° C., 30° C., 35° C., 40° C., 50° C., 60° C., 70° C., 80° C., 85° C., 90° C., 95° C., 100° C. The reaction time is 4-10 hours, for example, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours.
[0049] Wherein, the molar ratio of 2-(2-hydroxy-4-diethylaminobenzoyl)benzoic acid to 3,5-bis(trifluoromethyl)phenol is 1:(0.9-1.1), for example, 1:0.9, 1:0.95, 1:1, 1:1.05, 1:1.1.
[0050] The molar ratio of the mixed strong acid to 3,5-bistrifluoromethylphenol is 8:1-20:1. For example, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1. Specifically, the mixed strong acid is a mixture of concentrated sulfuric acid and trifluoromethylsulfonic acid, and the mass ratio of concentrated sulfuric acid to trifluoromethylsulfonic acid is 90:10-50:50. For example, 90:10, 80:20, 70:30, 60:40, 50:50.
[0051] Specifically, in step 2, the temperature is lowered to -1°C to 1°C, for example, -1°C, 0°C, 1°C.
[0052] In step 2, the organic solvent is one or more of toluene, o-xylene, m-xylene, mesitylene, unsymmetrical trimethylolene, and chlorobenzene. The alkaline solution is one or more of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, and ammonia water.
[0053] The heating temperature is 80-100° C., for example, 80° C., 85° C., 90° C., 95° C., 100° C. The reflux time is 0.5-2 hours, for example, 0.5 hours, 1 hour, 1.5 hours, 2 hours.
[0054] Specifically, in step 3, the drying temperature is 50-80° C., such as 50° C., 60° C., 70° C., 80° C. The drying time is 12 hours to 24 hours, such as 12 hours, 16 hours, 20 hours, 24 hours.
[0055] In the preparation method of the fluoran compound of the present invention, 2-(2-hydroxy-4-diethylaminobenzoyl)benzoic acid and 3,5-bistrifluoromethylphenol are used as reaction raw materials. The two reaction raw materials are reacted by the existing method, and the obtained product yield is low, which is only 27.35%. In the present invention, the two reaction raw materials are reacted in a mixed strong acid, and the product yield is increased to more than 70%.
[0056] In the preparation method of the present invention, the composition and dosage ratio of the mixed strong acid are optimized, thereby further ensuring that the product yield is increased to more than 69%, specifically 69.47%-72.94%.
[0057] Specifically, in step b, the stirring time is 0.5-2 hours, for example, 0.5 hours, 1 hour, 1.5 hours, 2 hours.
[0058] Specifically, in step c, the temperature for the static color test is 60-130°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C.
[0059] The color density values were recorded every 10°C.
[0060] In step a, preparing the developer dispersion includes: taking 8-12 parts of bisphenol A, 1-2 parts of polyvinyl alcohol, and 18-22 parts of deionized water, grinding to a dispersion d 50 The particle size was 0.80±0.05 μm, and a developer dispersion was obtained.
[0061] In step a, preparing the sensitizer dispersion includes: taking 8-12 parts of benzyl-2-naphthyl ether, 1.5-2.5 parts of polyvinyl alcohol, and 18-22 parts of deionized water, and grinding to a dispersion d 50 The particle size was 0.80±0.05 μm, and a sensitizer dispersion was obtained.
[0062] In step a, preparing the thermosensitive dye dispersion includes: weighing each raw material according to weight, mixing and grinding to a dispersion d 50 The particle size of the thermosensitive dye is 0.80±0.05 μm, and the thermosensitive dye dispersion is obtained.
[0063] Among them, 8-12 parts of fluorine-containing fluorane compounds, 1-5 parts of polyvinyl alcohol (PVA-205), and 15-25 parts of deionized water.
[0064] Specifically, the amount of the fluorane compound in the thermosensitive dye dispersion may be 8 parts, 9 parts, 10 parts, 11 parts, or 12 parts.
[0065] PVA-205 can be 1 part, 2 parts, 3 parts, 4 parts, or 5 parts.
[0066] The amount of deionized water can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, or 25 parts.
[0067] The present invention is described in detail below with reference to specific embodiments.
[0068] Example 1
[0069] Step 1: Add 2-(2-Hydroxyl-4-diethylaminobenzoyl)benzoic acid (CAS: 5809-23-4; 6.26 g, 0.02 mol), 3,5-bis(trifluoromethyl)phenol (CAS: 349-58-6; 4.60 g, 0.02 mol), concentrated sulfuric acid (20.00 g, 0.21 mol), and trifluoromethanesulfonic acid (CAS: 1493-13-6; 5.00 g, 0.03 mol) into a 250 ml three-necked flask equipped with mechanical stirring, and react at 75° C. for 6 hours;
[0070] Step 2: Add toluene (45.00 g) to the reaction system under an ice-water bath, then slowly add sodium hydroxide solution (50.00 g, 20 wt%), raise the temperature to 80° C., reflux and stir for 2 hours to obtain a reaction solution;
[0071] Step 3: Separate the liquids and collect the organic phase. Wash the organic phase with water until it is neutral and then separate the liquids. Collect the organic phase and remove toluene by distillation under reduced pressure. After drying, 7.31 g of a white, slightly powdery solid is obtained with a content of 99.20% (HPLC area method) and a yield of 72.03%. See Table 1.
[0072] The obtained fluorane compounds were subjected to nuclear magnetic resonance testing, and the specific results are as follows:
[0073] ( 1 H NMR(500MHz,Chloroform-d)δ7.97(dd,J=7.5,1.5Hz,1H),7.69(d,J=1.4Hz,1H),7.60(td,J=7.4,1.4Hz,1H),7.55(dd,J=7.5,1.6Hz,1H),7.51(td,J=7. 4,1.8Hz,1H),7.32(d,J=7.5Hz,1H),7.21(d,J=1.4Hz,1H),6.71(dd,J=7.5, 1.5Hz,1H),6.39(d,J=1.5Hz,1H),3.57–3.42(m,4H),1.17(t,J=8.0Hz,6H).)
[0074] Elemental analysis structure (molecular formula C 26 H 19F6NO3): Theoretical value: C, 61.54; H, 3.77; F, 22.46; N, 2.76; O, 9.46; Test value: C, 61.54; H, 3.98; F, 21.95; N, 2.86; O, 9.57.
[0075] Mass spectrum ESI-MS (m / z) (M+): theoretical value is 507.13, measured value is 507.32.
[0076] The results of elemental analysis show that the element ratio of the synthesized compound is basically consistent with the theoretical structure, and the mass spectrometry results show that the measured molecular weight is basically consistent with the theoretical structure molecular weight; 19 protons were detected after integration of the nuclear magnetic hydrogen spectrum, and the chemical structure can be determined based on the chemical shift of each signal, among which the 4 protons at 3.57–3.42ppm are attributed to the CH2 signals of diethylamino, the 6 protons at 1.17ppm are attributed to the CH3 signals of diethylamino, and the rest are proton signals in the aromatic ring of fluorane.
[0077] The above analysis and characterization prove that the product prepared by the method is a fluorine-containing fluorane compound with the structural formula of Formula I.
[0078] Example 2
[0079] Step 1: Add 2-(2-hydroxy-4-diethylaminobenzoyl)benzoic acid (6.26 g, 0.02 mol), 3,5-bis(trifluoromethylphenol) (4.60 g, 0.02 mol), concentrated sulfuric acid (20.00 g, 0.21 mol), and trifluoromethanesulfonic acid (20.00 g, 0.13 mol) into a 250 ml three-necked flask equipped with mechanical stirring, and react at 100° C. for 4 hours;
[0080] Step 2: Add toluene (45.00 g) to the reaction system under an ice-water bath, then slowly add sodium hydroxide solution (50.00 g, 20 wt%), raise the temperature to 100° C., reflux and stir for 0.5 hours to obtain a reaction solution;
[0081] Step 3: Separate the liquids and collect the organic phase. Wash the organic phase with water until it is neutral and then separate the liquids. Collect the organic phase and remove toluene by distillation under reduced pressure. After drying, 7.05 g of a white, slightly powdery solid is obtained with a content of 98.54% (HPLC area method) and a yield of 69.47%. See Table 1.
[0082] Example 3
[0083] Step 1: Add 2-(2-hydroxy-4-diethylaminobenzoyl)benzoic acid (31.33 g, 0.10 mol), 3,5-bis(trifluoromethylphenol) (25.31 g, 0.11 mol), concentrated sulfuric acid (120.00 g, 1.20 mol), trifluoromethylsulfonic acid (13.33 g, 0.09 mol) into a 500 ml three-necked flask equipped with mechanical stirring, and react at 25° C. for 10 hours;
[0084] Step 2: Add o-xylene (120.00 g) to the reaction system under an ice-water bath, then slowly add aqueous ammonia (170.00 g, 25 wt%), heat to 90° C., stir for 1 hour, and obtain a reaction solution;
[0085] Step 3: Separate the liquids and collect the organic phase. Wash the organic phase with water until it is neutral and then separate the liquids and collect the organic phase. Remove o-xylene by distillation under reduced pressure and obtain 35.77 g of a nearly white solid after drying. The content is 99.53% (HPLC area method) and the yield is 70.49%. See Table 1.
[0086] Example 4
[0087] Step 1: Add 2-(2-hydroxy-4-diethylaminobenzoyl)benzoic acid (31.33 g, 0.10 mol), 3,5-bis(trifluoromethylphenol) (23.01 g, 0.10 mol), concentrated sulfuric acid (120.00 g, 1.20 mol), trifluoromethylsulfonic acid (24 g, 0.16 mol) into a 500 ml three-necked flask equipped with mechanical stirring, and react at 60° C. for 8 hours;
[0088] Step 2: Add toluene (105.00 g) to the reaction system under an ice-water bath, then slowly add potassium hydroxide solution (340.00 g, 20 wt%), heat to 80° C., stir for 1 hour, and obtain a reaction solution;
[0089] Step 3: Separate the liquids and collect the organic phase. Wash the organic phase with water until it is neutral and then separate the liquids and collect the organic phase. Remove toluene by distillation under reduced pressure and obtain 37.01 g of a nearly white solid after drying. The content is 99.55% (HPLC area method) and the yield is 72.94%. See Table 1.
[0090] Comparative Example 1
[0091] This comparative example is substantially the same as Example 1, except that only concentrated sulfuric acid is added without adding trifluoromethanesulfonic acid. The yield is 27.39%, see Table 1.
[0092] Comparative Example 2
[0093] This comparative example is basically the same as Example 1, except that the mass ratio of concentrated sulfuric acid to trifluoromethylsulfonic acid in the mixed strong acid is 1:2, and the yield is 25.62%, see Table 1.
[0094] Comparative Example 3
[0095] This comparative example is basically the same as Example 1, except that the mixed strong acid is concentrated sulfuric acid and chlorosulfonic acid, and the yield is 25.82%, see Table 1.
[0096] Comparative Example 4
[0097] This comparative example is basically the same as Example 1, except that the reaction temperature in step 1 is 20° C. and the yield is 49.26%, see Table 1.
[0098] Comparative Example 5
[0099] This comparative example is basically the same as Example 1, except that the reaction temperature in step 1 is 110° C. and the yield is 65.12%, see Table 1.
[0100] Comparative Example 6
[0101] This comparative example is basically the same as Example 1, except that the temperature is raised to 60° C. in step 2, and the yield is 47.59%, see Table 1.
[0102] Comparative Example 7
[0103] This comparative example is basically the same as Example 1, except that the temperature is raised to 110° C. in step 2, and the yield is 50.27%, see Table 1.
[0104] Table 1 Yields of Examples and Comparative Examples
[0105] serial number Yield / % serial number Yield / % Example 1 72.03 Comparative Example 3 25.82 Example 2 69.47 Comparative Example 4 49.26 Example 3 70.49 Comparative Example 5 65.12 Example 4 72.94 Comparative Example 6 47.59 Comparative Example 1 27.39 Comparative Example 7 50.27 Comparative Example 2 25.62
[0106] It can be seen from Table 1 that in the process of preparing fluorine-containing fluorane compounds, not using mixed strong acid (Comparative Example 1), the proportion of mixed strong acid is not appropriate (Comparative Example 2), and the composition of mixed strong acid is not appropriate (Comparative Example 3) all have a great impact on the product yield.
[0107] It can also be seen from Table 1 that the inappropriate temperature of the condensation reaction (Comparative Example 4 and Comparative Example 5) and the inappropriate temperature of the condensation reaction (Comparative Example 6 and Comparative Example 7) will also have a great influence on the product yield.
[0108] Preparation Example 1
[0109] In this preparation example, the fluorine-containing light-stable fluorane compound of Example 1 is used as a thermosensitive dye, bisphenol A (BPA) is used as a developer, and benzyl-2-naphthyl ether (BON) is used as a sensitizer.
[0110] Take 10 parts of fluorine-containing light-resistant fluorane compound, 1.25 parts of PVA-205, and 20 parts of deionized water, and grind to a dispersion d 500.80±0.05μm, and obtain a thermal dye dispersion; take 10 parts of bisphenol A, 1.5 parts of PVA-205, and 20 parts of deionized water, and grind to a dispersion d 50 0.80±0.05μm, as the developer dispersion; take 10 parts of benzyl-2-naphthyl ether, 1.8 parts of PVA-205, and 20 parts of deionized water, and grind to a dispersion d 50 It is 0.80±0.05μm, used as a sensitizer dispersion.
[0111] Take 10 parts of the above-mentioned thermal dye dispersion, 15 parts of the developer dispersion, 7.5 parts of the sensitizer dispersion, 9 parts of kaolin, and 10 parts of deionized water, mix and disperse them for 1 hour using mechanical stirring, apply them on paper to prepare thermal paper, and perform a static color development test at 100°C. Record the color density value at every 10°C interval. The test results are shown in Figure 1 , Figure 2 and Table 2.
[0112] Preparation Example 2
[0113] This preparation example is basically the same as preparation example 1, except that the fluorine-containing light-stable fluorane compound of example 2 is used as the thermosensitive dye.
[0114] Preparation Example 3
[0115] This preparation example is basically the same as preparation example 1, except that the fluorine-containing light-stable fluorane compound of example 3 is used as the thermosensitive dye.
[0116] Preparation Example 4
[0117] This preparation example is basically the same as preparation example 1, except that the fluorine-containing light-stable fluorane compound of example 4 is used as the thermosensitive dye.
[0118] Comparative Example 8
[0119] This comparative example is basically the same as Preparation Example 1, except that the fluorine-containing light-resistant fluorane compound is replaced with 1,3-dimethyl-6-diethylaminofluorane (trade name: D-5). The test results are shown in Figure 1 , Figure 2 and Table 2.
[0120] Table 2. Test of light resistance of fluorine-containing light-resistant fluorane thermosensitive dyes
[0121]
[0122]
[0123] It can be seen from the data of the color density values before sunlight in Table 2 that the base colors of the thermal papers prepared in Preparation Example 1 and Comparative Example 8 before sunlight are basically the same (the color density values are similar when not colored, 0.10 and 0.09 respectively). After heating and color development, the color densities of the two are basically the same when saturated color is developed (1.30 and 1.33 respectively), which proves that the color development properties of the fluorane dye prepared in Example 1 are basically the same as those of the D-5 used in Comparative Example 8.
[0124] It can be seen from the color density values after 144 hours of sunlight exposure in Table 2 that after 144 hours of sunlight exposure, when there is no color development, the color density (base color) of the thermal paper in Preparation Example 1 does not change much compared with before sunlight exposure (increased from 0.10 to 0.12, an increase of 20%), and the base color of the thermal paper using D-5 in Comparative Example 8 has increased significantly (increased from 0.09 to 0.27, an increase of 200%), which is significantly higher than the color density value of the thermal paper in Preparation Example 1; after 144 hours of sunlight exposure, when the color is saturated, the saturated color density values of the thermal paper in Preparation Example 1 and the thermal paper using D-5 in Comparative Example 8 have both decreased to a certain extent. Specifically, the color density value of the thermal paper in Preparation Example 1 decreased from 1.30 to 1.17, a decrease of 10.0%, and the color density value of the thermal paper in Comparative Example 8 decreased from 1.33 to 0.98, a decrease of 26.3%. It is proved that after 144 hours of sunlight exposure, the base color and saturated color of the fluorane dye prepared in Preparation Example 1 are more stable than those of D-5, and has better light stability.
[0125] It can be seen from the data of Preparation Examples 2-4 in Table 2 that, similar to the data of Preparation Example 1, the color density change rates of the uncolored and saturated colored colors before and after sunlight exposure are not large.
[0126] In addition, by Figure 1 It can be seen that the absorption band of the fluorine-containing light-resistant fluoran-type thermosensitive dye prepared in Preparation Example 1 is consistent with that of the D-5 thermosensitive dye used in Comparative Example 8, proving that the macroscopic colors presented by the fluorine-containing light-resistant fluoran-type thermosensitive dye prepared in Preparation Example 1 and the D-5 thermosensitive dye used in Comparative Example 8 are basically consistent, and the two can be replaced under the premise of greatly adjusting the formula of the thermosensitive dye dispersion in most application scenarios. After the D-5 thermosensitive dye used in Comparative Example 8 is replaced by the fluorine-containing light-resistant fluoran-type thermosensitive dye prepared in Preparation Example 1, the thermosensitive material can have better light stability.
[0127] Depend on Figure 2 It can be seen that between 60°C and 130°C, the color density of the thermal paper of Preparation Example 1 is close to the color density of the thermal paper using D-5 in Comparative Example 8, proving that the color development of the two is basically the same in the entire temperature range, indicating that the performance of the fluorine-containing light-resistant fluorane thermal dye and the D-5 thermal dye in the dynamic color development performance test is basically the same, which can make the thermal materials used in dynamic thermal printing have better light stability.
[0128] The inventor has conducted a large number of experimental studies during the research process, and now uses some solutions with poor performance as comparative examples.
[0129] Comparative Example 9
[0130] This comparative example is substantially the same as Preparation Example 1, except that the amount of the thermosensitive dye dispersion is 13 parts.
[0131] Comparative Example 10
[0132] This comparative example is substantially the same as Preparation Example 1, except that the developer dispersion liquid is 19 parts.
[0133] Comparative Example 11
[0134] This comparative example is substantially the same as Preparation Example 1, except that the sensitizer dispersion liquid is 10 parts.
[0135] In Comparative Example 9, the weight portion of the heat-sensitive dye dispersion is too much, resulting in insufficient amounts of the developer and sensitizer, which is reflected in the low saturated color density and the saturated color development is not achieved at 130°C ( Figure 3 ), in order to determine its saturated color development ability, it is necessary to continue to increase the test temperature and collect more data points.
[0136] In Comparative Example 10, the weight of the developer dispersion is too much, resulting in a slightly higher color development at low temperature, and the color development in the temperature range of 90-100°C is too sensitive ( Figure 3 ), which is not conducive to evaluating the color-developing ability of the thermosensitive dye under low temperature or short-time heating conditions under this formula.
[0137] In Comparative Example 11, the weight of the sensitizer dispersion is too much, resulting in the overall color development curve shifting toward the low temperature direction, which is reflected in the fact that each temperature range is more sensitive, among which the color density at 60°C is close to 0.4, and the low-temperature color development performance of the thermosensitive dye under this formula cannot be evaluated.
[0138] It can be seen that inappropriate dosage of thermosensitive dye dispersion, developer dispersion and sensitizer dispersion will affect the static color test.
[0139] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for testing the static color development of thermal paper, characterized in that: The steps include: Step a: preparing a thermosensitive dye dispersion, a developer dispersion and a sensitizer dispersion respectively; Step b: Take 8-12 parts of thermosensitive dye dispersion, 12-18 parts of developer dispersion, 6-9 parts of sensitizer dispersion, 5-10 parts of kaolin and 8-12 parts of deionized water, mix and stir to obtain a mixed coating solution; Step c: applying the mixed coating liquid on paper, performing a static color development test, and recording the color density value; In step a, the raw materials for preparing the thermosensitive dye dispersion include a fluorine-containing fluorane compound having a structure of formula I:
2. The testing method according to claim 1, characterized in that: In step a, preparing the thermosensitive dye dispersion includes: weighing various raw materials according to weight parts, mixing and grinding, and obtaining the thermosensitive dye dispersion.
3. The testing method according to claim 2, characterized in that: By weight, the raw materials for preparing the thermosensitive dye dispersion liquid include: 8-12 parts of fluorine-containing fluorane compounds, 1-5 parts of polyvinyl alcohol, and 15-25 parts of deionized water.
4. The testing method according to claim 1, characterized in that: In step b, the stirring time is 0.5-2 hours.
5. The testing method according to claim 1, characterized in that: In step c, the temperature for the static color test is 60-130°C.
6. The testing method according to claim 5, characterized in that: In step c, the color density values are recorded once every 10°C.
7. The testing method according to claim 1, characterized in that: In step a, preparing the developer dispersion includes: taking 8-12 parts of bisphenol A, 1-2 parts of polyvinyl alcohol, and 18-22 parts of deionized water, and grinding to obtain the developer dispersion.
8. The testing method according to claim 1, characterized in that: In step a, preparing the sensitizer dispersion includes: taking 8-12 parts of benzyl-2-naphthyl ether, 1.5-2.5 parts of polyvinyl alcohol, and 18-22 parts of deionized water, and grinding to obtain the sensitizer dispersion.
9. The testing method according to claim 1, characterized in that: The fluorine-containing fluorane compound having the structure of formula I is prepared by the following method: Step 1: Add 2-(2-hydroxy-4-diethylaminobenzoyl)benzoic acid, 3,5-bis(trifluoromethylphenol) and a strong acid into a reaction container to cause a condensation reaction; Step 2: Cooling down, adding an organic solvent to the reaction system, and then slowly adding an alkaline solution, heating up, refluxing and stirring, causing a ring-closing reaction to occur, and obtaining a reaction solution; Step 3: Separate the reaction solution to obtain an organic phase, wash the organic phase with water until it is neutral, separate the phases, collect the neutral organic phase, remove the organic solvent by distillation under reduced pressure, and dry to obtain a solid fluorine-containing fluorane compound.
10. The testing method according to claim 9, characterized in that: In step 1, the strong acid is a mixed strong acid.